Long-term blood metal ion levels and clinical outcome after Birmingham hip arthroplasty - Pietiläinen Sakari; Lindström Miro; Laaksonen Inari; Venäläinen Mikko S.; Lankinen Petteri; Mäkelä Keijo T. (Finnish Surgical Society, 2022)
Background and objective: Our aim was to assess long-term metal ion level changes and clinical outcome in patients with a Birmingham hip arthroplasty. Methods: For the purpose of this study, we identified all BHR hip resurfacing arthroplasty (HRA) and total hip arthroplasty (THA) operations performed in Turku University Hospital. A random coefficient model was used to compare the change between the first and last metal ion measurement. A Kaplan-Meier estimator was used to assess the survivorship of the BHR HRA and BHR THA with metal related adverse events (pseudotumor, elevated metal ions above the safe upper limit, revision due to metallosis), or revision due to any reason as endpoints with 95% confidence intervals (CIs). Results: BHR HRA was used in 274 hips (233 patients). In addition, we identified 38 BHR-Synergy THAs (38 patients). Operations were performed between 2003 and 2010. Median follow-up time was 14 years for BHR HRA (range: 0.6-17) and 11 years for BHR THA (range: 4.7-13). In the BHR HRA group, geometric means of Cr and Co levels decreased from 2.1 to 1.6 ppb and 2.4 to 1.5 ppb, respectively, during a 3.0-year measurement interval. Metal ion levels in the BHR THA group did not show notable increase. The survivorship of BHR HRA was 66% in 16 years and 34% for BHR THA at 12 years for any metal-related adverse event. Conclusions: Patients with a Birmingham hip device do not seem to benefit from frequent repeated metal ion measurements. The amount of patients with metal-related adverse events was relatively high, but many of them did not require surgery.